Guru Penggerak in Merdeka Belajar - Sholeh, Badrus; Syarifudin, Encep; Suherman, Suherman (Jurnal Ilmiah Profesi Pendidikan, 2023)
Guru Pengerak is a significant program from ministry of education which has being implemented vastly to improve the quality of education. Guru penggerak is one of merdeka belajar policies. The purpose of this study was to examine the function of guru penggerak in the era of independent learning and to pinpoint the challenges they faced within the framework of Merdeka Belajar. The study used a library research methodology and performed a descriptive analysis on scientific articles from various journals. The findings showed that guru penggerak plays a significant role in the transformation of education from a centralized to a decentralized system. Guru Penggerak plays significant role as a transformational leader, motivator, and enhancer of teacher performance in carrying out instructional activities as well as a practical teacher for other teachers. Guru penggerak encounter challenges such as inadequate facilities, restricted internet access, and time restraints that reduce their effectiveness. Additionally, there is a lack of understanding of their role in schools, and some teachers may display indifference towards their activities. In conclusion, guru penggerak drives other teacher to escalate their competency for better education quality.